1996
DOI: 10.1002/(sici)1097-0363(19961115)23:9<953::aid-fld466>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Release of Gas From High-Pressure Pipelines

Abstract: The problem investigated is the break of a high‐pressure pipeline carrying natural single‐phase gas which may condensate (retrograde) when the pressure drops. Single‐phase non‐ideal gas is assumed using a general‐ ized equation of state. Taking advantage of the choked massflow condition, the break is split into a pipe flow problem and a dispersion flow problem, both solved using a finite difference control volume scheme. The transient flow field from the pipeline break location is expanded analytically, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…As boundary conditions for each of the regions shown by Figure 2 Some of the considerations used were that the system is in steady state, since the stabilization of the jet occurs in approximately [13], it was also considered that air entry and viscous forces in the expansion zone are negligible [20].…”
Section: Boundary Conditions and Solution Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As boundary conditions for each of the regions shown by Figure 2 Some of the considerations used were that the system is in steady state, since the stabilization of the jet occurs in approximately [13], it was also considered that air entry and viscous forces in the expansion zone are negligible [20].…”
Section: Boundary Conditions and Solution Methodsmentioning
confidence: 99%
“…They found that the CFD model produced encouraging results. Sand et al [20] and Novembre et al [21] studied accidental releases of natural gas in high-pressure pipelines. In their work, far-field dispersion was also investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Sand et al (Sand et al, 1996) extended the model by Birch et al by including an enthalpy equation and thereby making the unrealistic assumption of recovered temperature at the pseudo source plane unnecessary.…”
Section: Atmospheric Expansion Modelmentioning
confidence: 99%
“…Furthermore, the time step required for the transient CFD simulation of the jet appears to be in the range of 10 -7 s to 10 -5 s. For an overall CFD model including both the discharge and dispersion domains, the required computing time would be unacceptably long. Therefore the problem was divided into two parts [23,28,29], as shown in Fig. 8.…”
Section: Definition Of the Problemmentioning
confidence: 99%
“…Compared to the standard k- turbulence model, better agreement with the measurements in the prediction of the velocity profile was achieved by the modified k- model. Sand et al [28] and Novembre et al [29] studied accidental natural gas releases from high-pressure pipelines. In their work, far-field dispersion was also investigated.…”
Section: Introductionmentioning
confidence: 99%